2016
DOI: 10.22159/ajpcr.2016.v9i6.13798
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Anticancer Activity of Seaweeds Ulva Lactuca and Eucheuma Cottonii Against Breast McF-7 and Colon HCT-116 Cells

Abstract: Objective: This study is aimed to develop marine resources, which is focused on the determination of phytochemical composition and exploration of seaweeds Ulva lactuca and Eucheuma cottonii, as a potential antibreast cancer and anticolorectal cancer agents.Methods: Seaweeds U. lactuca collected from Parangtritis beach, Yogyakarta, Central Java, Indonesia, whereas E. cottonii collected from Salemo Island, South Sulawesi, Indonesia. Seaweeds U. lactuca and E. cottonii were macerated in organic solvents, n-hexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
(11 reference statements)
0
24
0
3
Order By: Relevance
“…The purified L-asparaginase showed good antioxidant activity on DPPH assay and provided a potential anticancer activity against MCF-7 cell line and should be considered for further pharmaceutical use as anticancer agents [38]. The results clearly demonstrate seaweeds Ulva lactuca and Eucheuma cottonii as promising candidates of new anti breast and anticolorectal cancer agents [39]. Pigmented rice serves as a good sources of antioxidant compounds, red rice varieties showed higher antioxidant properties and has health promoting properties as well as anti-cancer properties [40].…”
Section: Discussionmentioning
confidence: 99%
“…The purified L-asparaginase showed good antioxidant activity on DPPH assay and provided a potential anticancer activity against MCF-7 cell line and should be considered for further pharmaceutical use as anticancer agents [38]. The results clearly demonstrate seaweeds Ulva lactuca and Eucheuma cottonii as promising candidates of new anti breast and anticolorectal cancer agents [39]. Pigmented rice serves as a good sources of antioxidant compounds, red rice varieties showed higher antioxidant properties and has health promoting properties as well as anti-cancer properties [40].…”
Section: Discussionmentioning
confidence: 99%
“…8,19 Our previous research on red seaweed Euchema cottonii derived from South Sulawesi, Indonesia that demonstrated a strong cytotoxic activity against breast MCF-7 and colorectal HCT-116 cells, also containing metabolite of flavonoids. 10 Therefore, the mechanism of action of flavonoids as antioxidant and anticancer is a strong point of discussion in this work. Antioxidant systems are proposed to be involved in carcinogenesis because of its capability to damage the reactive oxygen species.…”
Section: Thin Layer Chromatography (Tlc) Of Eucheuma Cottoniimentioning
confidence: 99%
“…Method of extraction and fractionation of seaweed is adopted from previous research, 10 in which, 1000 g dry powder of macroalgae E. cottonii were macerated in ethyl acetate in a sealed glass vessel for a week, with conditional stirring. After maceration process, the filtrates were evaporated to give concentrated extract of Eucheuma cottonii.…”
Section: Extraction and Fractionation Samples Of Seaweedsmentioning
confidence: 99%
“…Maceration and extraction technique of Eucheuma cottonii is adopted 10 , as follows. Eucheuma cottonii is dried and ground to form a powder.…”
Section: Maceration and Extraction Of Eucheuma Cottoniimentioning
confidence: 99%
“…Some previous researchers has reported that Eucheuma cottonii demonstrated anticancer activity against MCF-7 breast cancer cells, HCT-116 colorectal cancer cells, and HeLa cervical cancer cells. [10][11][12][13] Beside that, Eucheuma cottonii are also widely cultivated in Indonesia, including in West Papua, with production level reached 6549 tons per year. 14 The anticancer activity and the large production of Eucheuma cottoni iin Indonesia has encouraged us to carry out phytochemical analysis, antioxidant activity, and cell line study of nutritious Eucheuma cottonii against lung A-549 cancer cells.…”
Section: Introductionmentioning
confidence: 99%